An efficient algorithm for computing safe exit points of moving range queries in directed road networks - Cho, Hyung-Ju; Ryu, Kiyeol; Chung, Tae-Sun (Information systems (Oxford), 2014)
In this paper, we investigate the problem of computing the safe exit points of moving range queries in directed road networks where each road segment has a particular orientation. The safe exit point of query object q indicates the point at which the safe region and non-safe region of q meet. A safe region indicates a region where the query result remains unchanged provided q remains inside this region. Unfortunately, the existing state-of-the-art algorithm focuses on computing the safe exit points of moving range queries in undirected road networks where every road segment is undirected. What is worse, far too little attention has been paid to moving range queries in dynamic road networks where the network distance changes depending on the traffic conditions. In this paper, we address these problems by proposing an efficient algorithm called CRUISE for computing the safe exit points of moving range queries in directed road networks. Our experimental results demonstrate that CRUISE significantly outperforms a conventional solution in terms of both computational and communication costs. •We propose a new algorithm to compute safe exit points for moving range queries in directed road networks.•We provide a comparative cost analysis of our algorithm and its competitor based on the assumption of undirected road networks.•We conduct extensive experiments to investigate the effects of various parameters using a real-life road dataset.